Psychology of preschool and school-age children and their study (Journal of Pedagogical Inventions and Practices, 2023)
The article talks about the psychological changes of children of junior school age. According to it, the child's adaptation to school and the period of mastering science in the educational process, as well as the impact of psychological changes in the process of adapting to a new environment, are considered.